The Future of the Map Library and Map Librarian - Moore, John N. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
Interest in maps and cartography is on the rise, partly spurred by new technologies such as Google Earth and Google Maps. But the new users, welcome as they are, do bring new challenges in terms of ease of use and speed of delivery. Therefore, LIBER's Groupe des Cartothécaires devoted its biennial conference to state-of-the-art technologies and concepts such as new retrieval techniques, Web 2.0 content, links with geospatial databases and FRBRisation to investigate their potential for and impact on map libraries and map librarians — whilst concluding that the particular expertise of a map librarian is as indispensable as ever. John Moore, the Group's Secretary, reports on the conference.